2008
DOI: 10.1097/psy.0b013e31815ff5c5
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Anxiety in Adults With Sickle Cell Disease: The PiSCES Project

Abstract: Depression and anxiety predicted more daily pain and poorer physical and mental quality-of-life in adults with SCD, and accounted for more of the variance in all domains of quality-of-life than hemoglobin type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
226
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(252 citation statements)
references
References 28 publications
22
226
3
1
Order By: Relevance
“…48 In SCD, the PISCES investigators found an association between the diagnosis of depression in SCD and lower quality-of-life outcomes on all 8 subscales of the SF-36. 37 The SCD Consortium report found HRQoL outcomes to be significantly worse on all subscales in adult SCD patients than in the general population. 49 Further, a strong association was found between the use of antidepressants, reflecting a diagnosis of depression and worse HRQoL outcomes on all scales except mental health.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…48 In SCD, the PISCES investigators found an association between the diagnosis of depression in SCD and lower quality-of-life outcomes on all 8 subscales of the SF-36. 37 The SCD Consortium report found HRQoL outcomes to be significantly worse on all subscales in adult SCD patients than in the general population. 49 Further, a strong association was found between the use of antidepressants, reflecting a diagnosis of depression and worse HRQoL outcomes on all scales except mental health.…”
Section: Discussionmentioning
confidence: 95%
“…9 In addition, adults with SCD who report more frequent painful episodes are more likely to report depressive symptoms. 37 Available evidence shows that affective disturbance and psychosocial factors are involved in negative medical outcomes, including increased frequency, duration, and intensity of painful episodes and adverse psychosocial consequences in patients with SCD. 7,11,[38][39][40] Further, negative or maladaptive cognitions, a particular feature of depression, are associated with poorer medical outcomes, passive adherence to medical directives, increased levels of psychological distress, and decreased capacity to cope with pain.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the patient's anxiety was, the more days he or she experienced pain, with or without pain crises. 9 Patients with sickle cell disease showed lower quality of life in mental component scores, compared with patients with cystic fibrosis, as well as lower scores in the "bodily pain, " "vitality" and "social functioning" domains, in comparison with asthma patients. 3 Compared with patients undergoing dialysis, sickle cell patients also showed less "bodily pain, " "general health" and "vitality".…”
mentioning
confidence: 92%
“…All pain is felt to be worsened by major psycho-social issues but this is consistently and well documented in individuals with SCD [13][14][15]. Like other chronic diseases that manifest in childhood (rheumatoid arthritis, cystic fibrosis), many sickle cell disease patients require frequent prolonged hospitalizations during childhood and adolescence that are barriers to education and the attainment of developmental milestones.…”
Section: Acute On Chronic Painmentioning
confidence: 99%
“…While many studies have associated mood disorders ranging from mania to major depressive disorder as predictors of higher utilization of resources, the literature is very inconclusive due to the research methods used and the populations studied [13,14,39]. Depression has been stated to be a predictor of higher utilization but when defined as a major depressive disorder as characterized in the Diagnostic and Statistical Manual of Mental Disorders (DSM), the association is not statistically significant [14,40].…”
mentioning
confidence: 99%